Single-cell and spatial transcriptomics reveal SPP1-CD44 signaling drives primary resistance to immune checkpoint inhibitors in RCC - Junfeng Zhang; Qingyan Peng; Jin Fan; Fuzhong Liu; Hongbo Chen; Xing Bi; Shuai Yuan; Wei Jiang; Ting Pan; Kailing Li; Sihai Tan; Peng Chen (Journal of Translational Medicine)
Abstract Background Immune checkpoint inhibitors (ICIs) are a cornerstone therapy for advanced renal cell carcinoma (RCC). However, significant rates of primary resistance hinder their efficacy, and the underlying mechanisms remain poorly understood. This study aims to unravel the tumor-immune interactions and signaling pathways driving primary resistance to ICIs in RCC. Methods We integrated single-cell RNA sequencing, spatial transcriptomics, and clinical sample analysis to investigate the tumor microenvironment and intercellular signaling. Advanced computational methods, including cell–cell communication networks, pseudotime trajectories, and gene set enrichment analysis (GSEA), were employed to uncover the underlying resistance mechanisms. Results Compared to the sensitive group, the primary resistance group exhibited a significant increase in SPP1-CD44 signaling-mediated interactions between tumor cells and immune cells. These interactions disrupted antigen presentation in immune effector cells and suppressed key chemokine and cytokine pathways, thereby impairing effective immune responses. In contrast, the sensitive group showed more active antigen presentation and cytokine signaling, which facilitated stronger immune responses. Furthermore, the interaction between SPP1-secreting tumor cells and CD44-expressing exhausted CD8 + T cells activated the MAPK signaling pathway within CD8 + Tex cells, exacerbating T cell exhaustion and driving the development of ICI resistance in RCC. Conclusion Our findings reveal a potential mechanism by which SPP1-CD44 signaling mediates tumor-immune cell interactions leading to ICI resistance, providing a theoretical basis for targeting and disrupting this signaling to overcome primary resistance in RCC.